Optimal Allocation of Distribution Automation Devices in Medium Voltage Network - Stojanović, M. S.; Tasić, D. S.; Ristić, A. T. (Elektronika ir Elektrotechnika, 2013)
In this paper a method for selection of optimal scenario for distribution automation is proposed. For a part of distribution network that can be considered as the smallest functional unit, the service zones are determined based on the heuristic rules, all possible automation scenarios are searched, and the values of selected objective functions are determined. After that, the four different methods are applied in evaluating a set of alternatives in terms of decision criteria: hybrid fuzzy-grey method, maximin method, simple additive weighting method and analytic hierarchy process. The method is demonstrated on test example of real medium voltage distribution network. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1351